The Influence Of Policy Intervention, Personal Factor, And Physical Environmental Factor On Pro-Environmental Behavior - Agustin Yolandari; Jahja Umar (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
Pro-environmental behavior is an act to protect and minimize the negative impacts of human activities on the environment. The purpose from this study is to determine whetherthere's influence from interventions policy, attitude towards pro-environmental behavior, subjective norm, perceived behavioral control (PBC), environmental knowledge (system knowledge, action related knowledge, and knowledge effectiveness), physical environmental factors (physical family environmental factor and physical society environmental factor), gender and age on pro- environmental behavior. The samples are 201 people who lives in Depok and South Tangerang, who has implemented an intervention policy called